Forests and Tribals - an Environment Impact Study - Chakrabarti, Kalyan (Indian Forester, 1996)
About 82 per cent of Indian tribal population live in Singhbhum, Keonjhar, Mayurbhanj, Sundergarh, Bastar, Chanda and several districts of Madhya Pradesh, Andbra Pradesh Eastern Gujarat and hills of Rajasthan; About 11 per cent of the tribal population live in Norlh-eastern Indian hills are suffering from the stress conditions caused by massive denudation due to shifting cultivation and other related factors, while the balance 7 per cent are distributed in the hills and plains of the country. Although Social Forestry has been a tool for socio-economic, economic and ecological development in this country and has raised 0.7 million hectares of plantation till date in the country mostly in non-forest areas, its impact (benefit or otherwise) on the tribal population oflndia has been insignificant. Environmental impacts brought about by hydroelectric dam projects, mining and other development projects have also not been studied so far in depth. In this paper the author had attempted to analyse the cause and effect and also the different facets of environmental impacts on the forest-fringe people in general and tribal population in particular with the object of creating a healthier environment and to improve the quality of life.